Judicial Analysis of the Powers and Functions of the Administrative Tribunals - Gupta, Sanjay; Sharma, Smriti (Christ University Law Journal, 2021)
Administrative tribunals are adjudicating bodiesestablished to relieve the traditional courts from the evermounting pressure of litigation. This paper makes ananalysis of the powers and functions of the administrativetribunals as laid down by the judiciary. A series of caselaws are examined at length which debate the nature ofthe functions of the tribunals and also elucidate theimportance of tribunals in dispensation of justice.